Attitudes toward Hormone Replacement Therapy in the New Millennium: University Physicians' and Patients' Perspectives. (1st September 2005) - Ismail, Hassan M.; Aleveritis, Ellie; Guha, Bhuvana; Olive, Kenneth; Sloan, Susan
Abstract : Background: Recent studies are changing the way physicians and patients view hormone replacement therapy (HRT). This study was performed at the East Tennessee State University (ETSU) internal medicine clinic to evaluate the current behaviors of university physicians and patients with respect to HRT. Methods: A retrospective chart review was conducted at the main internal medicine outpatient clinic at ETSU. Two hundred seventy-four postmenopausal female patients were randomly selected using a computerized systematic sampling technique of International Classification of Diseases, Ninth Revision (ICD-9) codes for menopause or postmenopause. The study period was from July 2002 until June 2004. Patients were postmenopausal women age 35 years or over who had been seen by their physicians at least twice a year during the study period. Patients who were noncompliant with HRT or physician's visits or had contraindications or side effects to HRT mandating discontinuation of the treatment were excluded. Data regarding physicians' patterns in discussion and discontinuation of the therapy and patients' responses were collected. Epi Info 2002 was used for statistical analysis. Results: One hundred seventy-seven patients met all of the criteria, of whom 140 were 35 to 75 years of age. Of this age group, 49 patients (35%) had coronary artery disease (CAD), 101 (72.1%) were on HRT prior to July 2002, and 30 (21.4%) had osteoporosis. Seventy-five patients (53.6%) had documented discussions with their physicians about HRT after July 2002. Most patients who were on HRT had no CAD (p = .0008). Of the patients who were on HRT, only 36 (35.6%) continued treatments (23 continued the same dose, and 13 had the dose modified), whereas 65 (64.3%) had treatments discontinued. HRT discussions were carried on mostly when patients had treatments stopped or modified (p = .0032). Of these patients who had discussions, 60 (80%) were advised to stop or modify the dose and agreed, and only 15 (20%) disagreed or received unbiased discussions from their physicians about HRT. Thiry-seven patients were over 75 years of age. This older group had a higher rate of HRT discontinuation (82%) but a lower rate of documented discussion (22%) than the younger group. Conclusion: Physicians should pay more attention to the importance of providing high-quality and well-balanced patient counseling when addressing uncertain treatments and adequately document discussions with patients in medical records.